ONGS e relações institucionais: primeiro, segundo e terceiro setores - Marina Félix de Melo (Universidade do Vale do Rio dos Sinos (UNISINOS), 2016)
This article seeks to shed light on the relationships that involve the operation of the third sector, particularly to see what are their points of connection with other variants of reality, viz. the state, the market and the third sector itself. Understanding how these relations have taken place is necessary because the entities tend to be involved in the formulation and implementation of social policies and actions, which isclosely related to the process of institutional professionalization of the third sector and specifically of NGOs.